Subjective, intersubjective, objective - Davidson, Donald, 1917-2003. (Oxford : Clarendon Press ; New York : Oxford University Press, 2001)
"Subjective, Intersubjective, Objective is the third volume of philosophical writings by Donald Davidson, whose influence on philosophy since the 1960s has been deep and broad. His first two collections, published by OUP in the early 1980s, are recognized as contemporary classics." "Now Davidson presents a selection of his work on knowledge, mind, and language from the 1980s and the 1990s. We all have knowledge of our own minds, knowledge of the contents of other minds, and knowledge of the shared environment. Davidson examines the nature and status of each of these three sorts of knowledge, and the connections and differences among them. Along the way he has illuminating things to say about truth, human rationality, and the relations among language, thought, and the world." "This new volume offers a rich and rewarding feast for anyone interested in philosophy today, and is essential reading for anyone working on its central topics."--BOOK JACKET.
First person authority (1984) -- Knowing one's own mind (1987) -- The myth of the subjective (1988) -- What is present to the mind? (1989) -- Indeterminism and antirealism (1997) -- The irreducibility of the concept of the self (1998) -- Rational animals (1982) -- The second person (1992) -- The emergence of thought (1997) -- A coherence theory of truth and knowledge (1983) -- Empirical content (1982) -- Epistemology and truth (1988) -- Epistemology externalized (1990) -- Three varieties of knowledge (1991).
Includes bibliographical references (p. [227]-231) and index.
Also available on the Internet to subscribing institutions.
Keywords: Knowledge, Theory of; Brain; Other minds (Theory of knowledge)